Imunoquímica de toxinas escorpiônicas que afetam canais para sódio: mapeamento de epitopos descontínuos - Clara Guerra Duarte (2011)
Scorpionism is still a worldwide health problem, even though there is a well stabilished treatment and good quality antivenoms available. Despite the evolution in the prepararation of antivenoms, the first step in this process, the immunization of animals, has not followed this development. The study of immunogens that are capable of eliciting neutralizing antibodies but that are not toxic for the producer animal would be of great interest. The identification of epitopes within an antigen isimportant for the characterization of antibodies, as well as for the generalunderstanding of the molecular basis of antigenicity and immunogenicity, and can be directly applied in the manipulation of the antigen to be used as an immunogen. The main goal of this work was to map, through a combined approach of bioinformatics and experimentation, discontinuous epitopes in scorpion toxins of medical and biotechnological interest, as AaH2 and Ts3, and anatoxins with neutralizing potential, TsNTxP and Amm8. Putative discontinuous epitopes were identified, using neutralizing antibodies generated by immunization with these proteins. The mapped epitopes apparently relate to the bioactive surface determined for the family of -toxins for voltage gated sodium channels, possibly accounting for its neutralizing potencial. The identification of such epitopes contributes for a better understanding of the immunochemistry of toxins and can help the development of new immunogens and creation of a new generation of immune products with improved specificity, safety and efficiency for the treatment of scorpion stings.